2019
DOI: 10.1172/jci131609
|View full text |Cite
|
Sign up to set email alerts
|

GPR101 mediates the pro-resolving actions of RvD5n-3 DPA in arthritis and infections

Abstract: N-3 docosapentaenoic acid–derived resolvin D5 (RvD5n-3 DPA) is diurnally regulated in peripheral blood and exerts tissue-protective actions during inflammatory arthritis. Here, using an orphan GPCR screening approach coupled with functional readouts, we investigated the receptor(s) involved in mediating the leukocyte-directed actions of RvD5n-3 DPA and identified GPR101 as the top candidate. RvD5n-3 DPA bound to GPR101 with high selectivity and stereospecificity, as demonstrated by a calculated KD of approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 30 publications
1
70
0
Order By: Relevance
“…Also, future studies may determine whether PLD2 activation is downstream of the recently identified target receptor of RvD5, GPR101. 74 In light of our findings that resolvins regulate PLD in inflammation resolution, we decided to further investigate using an in vivo model of rapidly progressing acute inflammatory response as in the setting of hind-limb ischemia/reperfusion injury. 49 Using this model of leukocyte mediated second organ injury, we evaluated how PLD and RvD5 regulate neutrophils, the first line of host defense, that rapidly and abundantly infiltrate sites of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Also, future studies may determine whether PLD2 activation is downstream of the recently identified target receptor of RvD5, GPR101. 74 In light of our findings that resolvins regulate PLD in inflammation resolution, we decided to further investigate using an in vivo model of rapidly progressing acute inflammatory response as in the setting of hind-limb ischemia/reperfusion injury. 49 Using this model of leukocyte mediated second organ injury, we evaluated how PLD and RvD5 regulate neutrophils, the first line of host defense, that rapidly and abundantly infiltrate sites of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a lipid mediator n-3 docosapentaenoic-derived resolvin D5 (7S,17S-dihydroxy-8E,10Z,13Z,15E,19Z-docosapentaenoic acid, RvD5n-3 DPA) has been shown to activate GPR101, representing a potential endogenous ligand to this previously orphan receptor ( 76 ). This bioactive lipid mediator enzymatically derived from essential fatty acid n-3 docosapentaenoic acid is a member of the specialized proresolving mediators.…”
Section: Genetic Mechanisms Of Tumorigenesismentioning
confidence: 99%
“…Most recently, N-3 docosapentaenoic acid-derived resolvin D5 (RvD5 n-3 DPA ), an autacoid, pro-resolving mediator, regulating inflammatory responses like arachidonic acid was reported as a putative ligand of GPR101 in macrophages and other monocytes (Flak et al 2020). Interestingly, knockdown of GPR101 reversed the protective actions of RvD5 n-3 DPA in limiting inflammatory arthritis, suggesting a potential role for GPR101 in the regulation of inflammation in leucocytes (Flak et al 2020). It remains unclear how these findings translate to the pituitary gland and hypothalamic GPR101 functions and require characterization in these tissues.…”
Section: Gnrh-(1-5) and Rvd5 N-3 Dpa : Putative Ligands?mentioning
confidence: 99%